2013
DOI: 10.1021/np300918q
|View full text |Cite
|
Sign up to set email alerts
|

Caesalpins A–H, Bioactive Cassane-Type Diterpenes from the Seeds of Caesalpinia minax

Abstract: Eight new cassane-type diterpenes, caesalpins A-H (1-8), were isolated from the ethyl acetate extract of Caesalpinia minax. Compound 1 displayed significant antiproliferative activity against HepG-2 (IC50 4.7 μM) and MCF-7 (IC50 2.1 μM) cells, and compounds 2 and 4 exhibited selective cytotoxic activities against MCF-7 (IC50 7.9 μM) and AGS (IC50 6.5 μM) cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
(28 reference statements)
0
32
0
Order By: Relevance
“…Caesall I (2) is, therefore, the 1-keto analogue of 1 and a perspective view of the molecular structure is presented in Fig. 1 C-NMR data were similar to caesalpin G, 8) except for the absence of one hydroxyl group, the presence of two acetoxy groups and the difference of the relative configuration at C-12. Three acetoxy groups were attached at C-1, C-2, C-3 respectively, on the basis of the HMBC correlations from H-1 (δ H (Fig.…”
Section: Hr-esi-ms ([M+ H]mentioning
confidence: 72%
See 2 more Smart Citations
“…Caesall I (2) is, therefore, the 1-keto analogue of 1 and a perspective view of the molecular structure is presented in Fig. 1 C-NMR data were similar to caesalpin G, 8) except for the absence of one hydroxyl group, the presence of two acetoxy groups and the difference of the relative configuration at C-12. Three acetoxy groups were attached at C-1, C-2, C-3 respectively, on the basis of the HMBC correlations from H-1 (δ H (Fig.…”
Section: Hr-esi-ms ([M+ H]mentioning
confidence: 72%
“…Previous phytochemical investigations on plants of Caesalpinia have resulted in the isolation of several cassane and norcassane furanoditerpenes, [6][7][8][9] and seven new compounds, caesalls A-G, 10) were isolated in our previous research on C. bonduc. As a continuation of our study on this plant, the ethanol (95%) extract of the seed kernel was investigated.…”
Section: -5)mentioning
confidence: 99%
See 1 more Smart Citation
“…The HRESIMS spectrum demonstrated a quasi-molecular ion at m/z 454.2199 (Calcd for C24H33NO6Na, 454.2206), which in connection with the NMR data, confirmed that the molecular formula was C24H33NO6. The IR and UV spectra revealed absorptions for an amidogen (3190 cm −1 ), a carbonyl (1735 cm −1 ), and an α,β-unsaturated butenolide unit (210 nm; 1749 cm −1 ) [2]. The 1 H and 13 C APT NMR spectra (Table 1) displayed the olefinic proton signal at δH 5.86 (H-15, s) and four downfield-shifted carbon signals at δC 107.4 (C-12), 171.0 (C-13), 115.9 (C-15), and 179.9 (C-16), which also confirmed the presence of the α,β-unsaturated butenolide ring.…”
Section: Structure Elucidation Of Compounds 1-2mentioning
confidence: 99%
“…Previous phytochemical investigations indicated that this genus contains an abundant source of cassane diterpenes with different structure types, and most of them showed in vitro or in vivo pharmacological impacts such as antiproliferative [1][2][3], antiplasmodial [4][5], antibacterial [6], antihelmintic, and antineoplastic activity [7]. As a continuation of our project towards new bioactive diterpenes discovery from the genus Caesalpinia [2][3]8], we examined the chemical constituents of C. sappan and obtained two new cassane diterpenes, designated caesalsappanin R (1) and caesalsappanin S (2) (Figure 1). Compound 1 is a rather unusual cassane diterpenoid lactone-type skeleton, consisting of an N bridge between C-19 and C-20.…”
Section: Introductionmentioning
confidence: 99%